(untitled) (Research, Society and Development, 2021)
The objective of this article was to characterize the patients seen at the Outpatient Clinic of the Special Immunobiological Infusion Center at the State University of Rio de Janeiro. This is a cross-sectional, retrospective study with quantitative analysis of data from the patients’ physical records. The sample consisted of 96 patients over 15 years of age undergoing treatment and monitoring for chronic autoimmune diseases since 2014. There was a predominance of females (54.2%), with the age group between 21 and 50 years old concentrates more than half of the patients (51.1%). The level of education that prevails is complete high school (65.6%), with most patients residing in the city of Rio de Janeiro (88.3%). Chronic and autoimmune diseases in follow-up are related to the medical specialties gastroenterology (72.6%), allergy (24.5%) and pulmonology (2.8%). There was a low rate of local or systemic reactions related to infusions, with maintenance of treatment followed by precaution by the team and that although certain patients have progressed to death, it cannot be said for sure that these were related to the use of prescribed immunobiologicals.